Evaluating customer satisfaction, emotion and experience of smart hotels in Zhejiang, China: an analysis of online reviews / Chen Jie, Wang Qian and Faiz Izwan Anuar - Chen, Jie; Wang, Qian; Faiz Izwan, Anuar (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
With the rapid advancements in information technology, the integration of big data management across various sectors is becoming ubiquitous. Recent trends show that hotels in Zhejiang Province are increasingly adopting big data management techniques encompassing data analytics, customer relationship management, and strategies to enhance customer satisfaction. This study explores the domain of smart hotels, specifically examining customer satisfaction measures linked to these innovative establishments in Zhejiang Province. Moreover, it seeks to identify disconnects between technical intelligence and customer satisfaction within smart hotels and to outline prospective developmental trends. The study draws upon customer reviews collated from online platforms, scrutinizing expected outcomes like overall satisfaction, emotional reactions, and the technical adaptability encountered by guests at these smart hotels. Our findings of the study reveals that customers generally express contentment with their smart hotel experiences, particularly valuing the technological atmosphere and the accessibility of smart features. However, the findings also illuminate prevailing challenges, such as irregularities in smart device functionality, a deficiency in perceived cutting-edge intelligence within the hotels, and a shortfall in meeting unique customer needs. Advancing the progression of smart hotels necessitates a focus on enhancing the guest experience by integrating critical factors—environmental, service, and value—alongside insightful customer feedback to refine and shape customer satisfaction.